ABSTRACT The increasing of human demand about diesel fuel that was not balanced with the appropriate of petroleum production caused global crisis of energy. Under these conditions, biodiesel is a promising alternative fuel to replace petroleum-based diesel. Jatropha curcas L. can be used as an alternative energy resource because it contains 30-40% oils. Jatropha curcas L. is a plant that can be easily growned in Indonesia, so it is prospective as raw material for biodiesel. The purpose of this - Fitriyana Ayu Aprilyanti dan Ika Amalia Kartika (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT   The increasing of human demand about diesel fuel that was not balanced with the appropriate of petroleum production caused global crisis of energy. Under these conditions, biodiesel is a promising alternative fuel to replace petroleum-based diesel. Jatropha curcas L. can be used as an alternative energy resource because it contains 30-40% oils. Jatropha curcas L. is a plant that can be easily growned in Indonesia, so it is prospective as raw material for biodiesel. The purpose of this study was to determine the influence of reaction time and hexane to total solvent ratio on biodiesel yield and quality produced by in situ transesterification of jatropha seeds. The used raw material was grounded jatropha seeds with moisture content of < 2% and ± 20 mesh size. The operating conditions of hexane to total solvent ratio and reaction time were varied at 1/6, 2/6, 3/6 and 3, 4, 5 h, respectively. KOH concentration, reaction temperature and stirring speed were fixed at 0.075 mol/L methanol, 55oC and 300 rpm. The analysis of biodiesel quality included acid value, viscosity, ash content and saponification value. The results were analyzed with Response Surface Method (RSM). The produced biodiesel yield was 71%-81%. The highest yield (80.67%) and the best quality of biodiesel were obtained under operation condition of the 5 h reaction time and 1/6 hexane to total solvent ratio (acid value of  0.31 mg KOH/g, saponification value of 193.97 mg KOH/g, viscosity of 3.45 cSt, and ash content of 0%). Respon surface analysis of hexane to total solvent ratio and reaction time variables to respon of biodiesel yield resulted first order equation, Y =  63.00– 4.14(A) + 3.81(B), with R2= 95.56%. The variable of reaction time (B) had significant influence on biodiesel yield. Respon surface analysis of operating condition variables to respon of biodiesel quality showed the variable of hexane to solvent ratio (A) and reaction time (B) had significant influence on acid value and viscosity, especially.   Keywords: biodiesel, jatropha, in situ transesterification, reaction time, solvent ratio